Encyclopaedia Britannica almanac 2006. - 4 0 16; 5 Encyclopaedia Britannica, inc. (Chicago : Encyclopaedia Britannica, 2005)
Presents a complete almanac that provides information on key people, events, places, awards, discoveries, and developments from 2006, and includes a CD-ROM with additional facts.
Includes index.
Wilson's Junior High School
Young Adult;Young Adult
System requirements for computer disc: Pentium/266MHz; 128MB RAM; 170MB free HD space; WIN 98/WIN Me/WIN 2000/WIN XP; 16-bit col. display; CD-ROM drive; mouse; sd. card.;System requirements for computer disc: PowerPC G3/350MHz+; 128MB RAM; 170MB free HD space; System 10.22; CD-ROM drive; mouse; sd. card.
Keywords: 2 -- 0; 6; Almanacs.;Almanacs.; 20; 2